1991
DOI: 10.3109/00365529108996485
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Studies after Ileal J-Pouch Anastomosis for Ulcerative Colitis: A Prospective Study

Abstract: Absorption studies were performed in 17 patients with ulcerative colitis operated on with colectomy and an ileal two-limbed J-pouch anastomosis. The patients were studied 3 and greater than or equal to 18 months after closure of the temporary ileostomy. Increased stool mass (median, 609 g/24 h) was found in all patients and was unchanged with time. Moderate steatorrhoea was present in 29% of the patients 3 months postoperatively, but faecal fat excretion normalized with time. Calcium absorption was normal in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…These findings may be related to disturbances in mucosal repair. The increased production of cytokines such as IL-1β and TNF-α in the H. pylori -infected gastric tissues thereby causing a disturbance in mucosal repair may support the present finding [3, 35]. However, to elucidate which of the MAP kinases is activated by stimulation of H. pylori , another experiment is needed next.…”
Section: Discussionmentioning
confidence: 59%
“…These findings may be related to disturbances in mucosal repair. The increased production of cytokines such as IL-1β and TNF-α in the H. pylori -infected gastric tissues thereby causing a disturbance in mucosal repair may support the present finding [3, 35]. However, to elucidate which of the MAP kinases is activated by stimulation of H. pylori , another experiment is needed next.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, clinical signs of malnutrition or malabsorption are rare in these patients (77). Low vitamin B12 levels and decreased Schilling tests have been found in patients with ileal pouch-anal anastomosis (57,74,82).…”
Section: Malabsorptionmentioning
confidence: 99%
“…Hylander et al (82) found moderate steatorrhea in approxi mately 30% of patients 3 months after ileostomy closure, but fecal fat excretion normalized with time. The absorption of carbohydrates, amino acids, and bile acids by the ileal pouch mucosa after proctocolectomy with ileal pouch-anal anasto mosis has been found to be markedly decreased compared to normal ileum (83).…”
Section: Malabsorptionmentioning
confidence: 99%
“…Earlier studies show that the ileoanal anastomosis may disturb bile acids absorption. 19,20 Patients with IAA show a reduced biliary secretion of bile acids and reduced masses of cholesterol, bile acid, phospholipids. [21][22][23] In particular the deoxycholic acid is significantly reduced in patients with IAA.…”
Section: Discussionmentioning
confidence: 99%